Rekonstruksi Perjuangan Zapatista Di Meksiko Dalam Lagu Bayang Tak Berwajah Oleh Geekssmile - Kusuma, Arya Pramana; Amanda Gelgel, Ni Made Ras; Dewi Pascarani, Ni Nyoman (E-Jurnal Medium, 2019)
ABSTRACT The purpose of this research to determine thereconstruction of the zapatista struggle in Bayang Tak Berwajah music lyric from band named Geekssmile . This reasearch uses a qualitative semiotic approach. The technique of determining informants in this study used a purposive technique. Data obtained through in-depth interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion. Geekssmile wants to spread the message about how the negative impact of an armed conflict. Geekssmile wants to educate they listeners that war is a bad thing and must be avoided, because it only brings obscurity and evil. So that the listeners are not easily provoked and carried away in a of unfavorable conflict. Keywords: Geekssmile, semiotic, message, music lyric